Perbedaan Kompetensi Pedagogik dan Kompetensi Profesional Guru Bimbingan dan Konseling - kurniadi, eka; wibowo, mungin eddy (Universitas Negeri Semarang, 2016)
This study was conducted based on the phenomenon that occurs in the guidance and counseling teacher graduates of state universities and private colleges in Pemalang district Junior High School. The purpose of this study was to prove there any differences in pedagogical competence and professional competence of guidance and counseling teacher graduates of state universities and private colleges. This research is a comparative study with teacher guidance and counseling 40 subjects. The data collection method used was a questionnaire about pedagogical competence and professional competence of guidance and counseling teacher. Data were analyzed using descriptive analysis of the percentage and t-test. The results showed no difference in the average and the percentage of each component. It shows that there are differences in the implementation of pedagogic and professional competence between guidance and counseling teacher graduates of state universities and private colleges in Pemalang district Junior High School.